Pengaruh Celebrity Endorser dan Brand Image terhadap Keputusan Pembelian pada Produk Kosmetik Wardah di Kota Palembang - Elsalonica, Carla Mourina; Elpanso, Efan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the influence of celebrity endorsers and brand image on purchasing decisions on wardah cosmetic products in Palembang City. The population in this study were wardah customers in Palembang City, 90 samples were taken. The data collection method used in this study was obtained through a questionnaire. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis it was concluded that celebrity endorsers and brand image have a positive and significant partial effect on purchasing decisions on wardah cosmetic products in Palembang City. Through a simultaneous test, the results of celebrity endorser and brand image have a positive and significant simultaneous effect on purchasing decisions on wardah cosmetic products in Palembang City.